Electroless plating : a technique for the preparation of supported cobalt and gold catalysts - Beetge, Johannes Albertus (My University, 2016)
The preparation of supported cobalt and gold catalysts by the technique of electroless plating, and the establishment of the influence of synthesis variables on the physical properties of the supported catalyst, forms the basis of this dissertation. In both the cases of cobalt and gold supported on extruded cylindrical alumina pellets, the penetration profile of the metal into the support showed dependence on the pH of the activation solution, while the metal loading onto the same support showed no dependence on pH of the activation solution at all. The variables involved in the plating process of the activated pellets, namely: i) the concentration of the activation solution, ii) pH and temperature of the plating bath, iii) plating time, and Iv) variation of the concentrations of components of the plating bath all influenced the mass of metal loaded onto the support, but not the penetration characteristics. It is therefore possible to prepare a supported catalyst with very specific , properties using the above information. Under similar conditions, with extruded alumina pellets as support and with the specific plating formulations used, gold showed higher metal loadings at lower gold concentrations than cobalt.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Master of Science. November 1995.
Keywords: Electroless plating.; Cobalt catalyst.; Gold.; Catalysts.